2004
DOI: 10.1016/j.str.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Superoxide Reductase Bound to Ferrocyanide and Active Site Expansion upon X-Ray-Induced Photo-Reduction

Abstract: Some sulfate-reducing and microaerophilic bacteria rely on the enzyme superoxide reductase (SOR) to eliminate the toxic superoxide anion radical (O2*-). SOR catalyses the one-electron reduction of O2*- to hydrogen peroxide at a nonheme ferrous iron center. The structures of Desulfoarculus baarsii SOR (mutant E47A) alone and in complex with ferrocyanide were solved to 1.15 and 1.7 A resolution, respectively. The latter structure, the first ever reported of a complex between ferrocyanide and a protein, reveals t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
122
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 53 publications
(2 reference statements)
9
122
0
1
Order By: Relevance
“…The recent crystal structure of SOR from D. baarsii revealed that the organometallic compound ferrocyanide makes a complex with the enzyme active site (8). This structure is the only example of a complex between ferrocyanide and an iron site of a metalloenzyme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recent crystal structure of SOR from D. baarsii revealed that the organometallic compound ferrocyanide makes a complex with the enzyme active site (8). This structure is the only example of a complex between ferrocyanide and an iron site of a metalloenzyme.…”
Section: Discussionmentioning
confidence: 99%
“…1). The complex was observed for both the reduced and oxidized forms of the SOR iron active site (8). The almost perfect steric and electrostatic complementarities of ferrocyanide with the active site suggested that it could act as a potent inhibitor of SOR activity by preventing O 2 .…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…In another example, reduction of the haem iron by synchrotron radiation followed by transient warming to room temperature was used to generate and trap intermediate states in crystalline myoglobin (Hersleth et al, 2008). Research on other crystalline redox-sensitive proteins for which X-rayinduced reduction has been reported at temperatures close to 100 K (Berglund et al, 2002;Adam et al, 2004;Baxter et al, 2004;Mees et al, 2004;Roberts et al, 2005;Echalier et al, 2006;Beitlich et al, 2007;Kuhnel et al, 2007;Pearson et al, 2007;Hough et al, 2008) could benefit from temperaturecontrolled crystallography if structural information on intermediate states were of interest.…”
Section: Temperature-controlled Kinetic Cryocrystallography To Characmentioning
confidence: 99%